The state of public sector ICT infrastructure in Zimbabwe and its implications on service delivery. - Duve, Richard; Viljioen, Jan W. J.; Tambudzai, Zachary (Midlands State University, 2017)
This paper seeks to establish the current state and government support of ICT infrastructure development and modernisation as enabling tools to enhance service delivery to the Zimbabwean citizens as they transact with government departments. This paper focuses on ICT infrastructure at ZIMRA, Immigration, ZINARA, Registrar General’s departments of Births and Deaths and Passports offices. Mixed method research design was used in this research. Questionnaires, interviews and observations were the research instruments used to collect data from 1191 research subjects. The Pearson Chi-square statistic was also used to test the themes that emerged from the research questionnaires and interviews. The research findings indicate that current ICT infrastructure in Zimbabwe is now inadequate, fragmented and uncoordinated, especially at ports of entry and other government departments under study. The research findings also show that whilst government is committed to ICT infrastructure development and modernization in the public sector, funding is the limiting factor.